Establishment and Chimera Analysis of 129/SvEv- and C57BL/6-Derived Mouse Embryonic Stem Cell Lines - W. Auerbach; J.H. Dunmore; V. Fairchild-Huntress; Q. Fang; A.B. Auerbach; D. Huszar; A.L. Joyner (BioTechniques)
Hundreds of new mutant mouse lines are being produced annually using gene targeting and gene trap approaches in embryonic stem (ES) cells, and the number is expected to continue to grow as the human and mouse genome projects progress. The availability of robust ES cell lines and a simple technology for making chimeras is more attractive now than ever before. We established several new ES cell lines from 129/SvEv and C57BL/6 mice and tested their ability to contribute to the germline following blastocyst injections and/or the less expensive and easier method of morula-ES cell aggregation. Using morula aggregation to produce chimeras, five newly derived 129/SvEv and two C57BL/6 ES cell lines tested at early passages were found to contribute extensively to chimeras and produce germline-transmitting male chimeras. Furthermore, the two 129S/vEv ES cell lines that were tested and one of the C57BL/6 ES cell lines were able to maintain these characteristics after many passages in vitro. Our results indicate that the ability of ES cells to contribute strongly to chimeras following aggregation with outbred embryos is a general property of early passage ES cells and can be maintained for many passages. C56BL/6-derived ES cell lines, however, have a greater tendency than 129-derived ES cell lines to lose their ability to colonize the germline.